2016
DOI: 10.1177/0300060516666229
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of oestrogen receptor expression in non-small cell lung cancer

Abstract: ObjectiveTo investigate the expression and clinicopathological significance of the oestrogen receptor (ER) in non-small cell lung cancer (NSCLC).MethodsER expression was examined by immunohistochemical staining of tumour tissue and adjacent normal lung tissue from 67 NSCLC patients. The relationships between ER expression and clinicopathological features were analysed.ResultsA higher percentage of NSCLC tissues (28/67, 41.79%) than adjacent normal lung tissues (10/55, 18.18%) were ER positive. ER expression co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…In the present study, there were no significant associations between sex and the expression of ERα, or nuclear or cytoplasmic ERβ. ERβ expression has been demonstrated to be positively correlated with the degree of lung cancer differentiation ( 32 ), and a positive association between nuclear ERβ expression and tumor differentiation was also observed in the present study. This suggests that ERβ expression may, to a certain extent, reflect the degree of malignancy and therefore may be used as a predictor of prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, there were no significant associations between sex and the expression of ERα, or nuclear or cytoplasmic ERβ. ERβ expression has been demonstrated to be positively correlated with the degree of lung cancer differentiation ( 32 ), and a positive association between nuclear ERβ expression and tumor differentiation was also observed in the present study. This suggests that ERβ expression may, to a certain extent, reflect the degree of malignancy and therefore may be used as a predictor of prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…No significant difference in the clinicopathological characteristic between the ERβ-positive and ERβ-negative lung adenocarcinoma has been mentioned, except some reported that the ER expression correlated with the tumor differentiation [ 111 ]. Detailed pathologic examination of the ERβ-positive adenocarcinoma may be necessary to show the genotype-phenotype correlations, similar to those found in the ALK-rearranged or the EGFR-mutated adenocarcinoma [ 112 , 113 ].…”
Section: Er As Targets For Lung Cancer Therapy and Relationship Wimentioning
confidence: 99%
“… 51 TransPRECISE implicated the hormone receptor pathway in lung cancer, which is another known observation that is being studied for its translational potential. 52 Our sample-specific inference of pathway activity provided robust tumor stratification across model systems that include distinct prognostic information ( Fig 5 ). These robust edges and cross-signaling of pathways across model systems and cancer sites will potentially provide complementary information in terms of disease characterization and therapeutic targets.…”
Section: Discussionmentioning
confidence: 93%